Two noteworthy ramicolous liverworts from Mount Roraima, Guyana: Frullania trigona and Metzgeria deniseana sp. nov. - Gradstein, S. Robbert; Ilkiu-Borges, Anna Luiza (Phytotaxa, 2021)
Mount Roraima, at the geographical tripoint of Brazil, Guyana and Venezuela, is famous for its richness in rare and endemic species. Here we report two unusual ramicolous liverwort species from the north ridge of the mountain, located within the borders of the country of Guyana: Frullania (sect. Microphyllae) trigona and Metzgeria deniseana sp. nov. Frullania section Microphyllae is a group of ten species within subgenus Frullania, distributed in eastern Asia, Europe and tropical America, and characterized by the small dioicous plants with ocelli, caducous leaf lobes and tiny underleaves. Frullania trigona is one of the rarest species of the section and was only known from the type collection from Guadeloupe. It is recognized by the obclavate lobules with a very small mouth, leaf margins with protruding whitish trigones and the presence of a huge attachment cell at the dorsal leaf bases. The latter two features are unusual in Frullania and are unique to F. trigona. Metzgeria deniseana is a new member of the genus Metzgeria with saccate thallus lobes (= former genus Austrometzgeria) and stands out by the very irregular shaped sacs, varying from subglobose to strongly elongate, thallus margins with a wide and ill-defined border, and strongly convex gemmae with revolute margins. The discovery of Frullania trigona and Metgeria deniseana adds two further noteworthy species to the rich liverwort flora of Mount Roraima.